Collision Avoidance Regulation-Compliant Orientation Guidance and Maneuvering Control Approach for Snake Robots - Xiu, Yang; Deng, Hongbin; Li, Dongfang; Law, Rob; Wu, Edmond Q.; Zhu, Limin (IEEE transactions on industrial electronics (1982), 2024)
Snake robots under environments with avoidance constraints hardly track routes such that traditional guidance approaches become infeasible. Motivated by it, this work presents a line-of-sight-guidance virtual-snake-robot integrated scheme for snake robots to track paths and obey collision avoidance regulations. Main contributions include the avoidance regulation-compliant kinematics guidance law and finite-time-converged adaptive dynamic controller. In kinematics, a virtual leader is used to optimize nondifferentiable inflection into smooth to provide a jitter-free direction. Considering avoidance constraints, corresponding guidance strategies are innovatively designed for head-on, overtaking, and crossing scenarios to ensure the safety and autonomy of path tracking. In terms of dynamics, maneuvering control is executed by a finite-time disturbance observer-based event-triggered terminal sliding-mode controller. The unmeasured errors and uncertainties are accurately compensated, and input event-triggering rules can reduce the actuator burden. Finally, the stability analysis proves system errors' finite-time convergence, and result validations confirm the performance superiority and feasibility of this method.